The Differences of Cholesterol Level in DMPA (Depo Medroxy Progesteron Acetat) and Cyclofem Injection Acceptors - Rahayu, Esty Puji; Munjidah, Annif (Journal of Global Research in Public Health, 2020)
The latest data on the coverage of active FP participants Contraceptive Prevalence Rate (CPR) in Indonesia reaches 61.4%, and this figure is quite a high achievement rate among ASEAN countries. However, the methods used are mostly short-term methods such as pills and injections. According to data from Indonesian health resources, family planning acceptors who use injections are 30.8%, pills 13.2%, IUDs 4.8%, implants 2.8%, tubectomy 3.1%, and condoms 1.3%. One of the methods of injection KB that is widely used is Depo Medroxyprogesterone Acetate (DMPA) and Cyclofem. Unlike the contraceptive Cyclofem which does not interfere with the menstrual cycle because of the presence of estrogen in cyclofem, DMPA injectable contraception has side effects, namely causing the hormone estrogen to be imbalanced because DMPA only contains progesterone, causing a decrease in HDL (High Density Lipoprotein) and an increase in LDL (Low Density Lipoprotein). ) this will result in an increase in total cholesterol. In this study, the research design used was a comparative analysis, namely comparing cholesterol levels in DMPA and Cyclofem acceptors. This study used a cross sectional study. The population was DMPA and Cyclofem injection family planning acceptors, while the sampling technique used purposive sampling technique. Based on the results of data analysis with the Paired T test, it was found that DMPA acceptors had higher cholesterol levels (mean = -1.822; SD = 45.34; p <0.005) than cyclofem acceptors (mean = 1.722; SD = 35.51; P <0.005). Contraceptive injections cause changes in fat metabolism through changes in HDL and LDL levels. HDL is antiatherogenic, on the other hand, high levels of LDL and triglycerides cause cardiovascular disease in the periphery and coronary arteries which cause cardiovascular disease. Long-term use of hormonal contraceptives causes an increase in LDL, whereas HDL varies